La dislalia funcional y su incidencia en la autoestima de los escolares de cuarto año de educación general básica de la unidad educativa “Pio Jaramillo Alvarado” periodo 2018. - Gabriela Geovanna, Lima Ojeda (2019)
The following investigation research named: Functional dyslalia and its incidence in the self-esteem of the fourth year students of basic general education at "Pio Jaramillo Alvarado" Elementary School in the period of 2018, is intended to correct the pronunciation in schoolchildren with dislalia Functional and at the same time to improve the self-esteem of children from seven to eight years old, as regards the general objective is: to determine how the functional dyslalia affects the self-esteem of the fourth grade students of "Pio Jaramillo Alvarado" Elementary School in the period of 2018.This is a research of a social scientific manner of a descriptive nature with a qualitative approach. The methods used are scientific, qualitative and analytical-synthetic, the information was collected by means such as: Observation sheet for the functional dyslalia applied to six children of fourth grade that was elaborated by the author of the research, besides the test for articulated repetition ART for dyslalia and the Lucy Reidl Self-Esteem Scale for selfesteem was used. The results allowed us to conclude that the functional dyslalia in the fourth-grade children, is evident because of their bad pronunciation, mainly in the substitution and omission of a phoneme for another one. Despite we can say that most schoolchildren have a good self-esteem, which is fragile at times when they make mistakes and feel embarrassed, so it is recommended that the authorities of this Institution, can maintain these types of activities in the way possible, so that these activities have given positive results in the phonological development of schoolchildren.